Estimation of Water Saturation in Shale Formation Using In Situ Multifrequency Dielectric Permittivity - Yongchae Cho; Sean S. Dolan; Nishank Saxena; Vishal Das (Geofluids)
Estimating water saturation via conventional logging tool such as resistivity cannot provide an accurate solution in a formation with low conductivity water and tight porosity. As an alternative, we employed a dielectric permittivity, which makes it easy to differentiate the water from the other fluids in pore structures. A multichannel frequency dielectric logging tool is used for measuring in situ permittivity. To simulate a dielectric permittivity, we used two analytic models: Lichtenecker-Rother (LR) and Stroud-Milton-De (SMD) models. The key goal of this research is to propose a workflow to evaluate an equivalent Archie’s parameter which can generate the same dielectric logging tool responses with core measurement results using a given analytic models. According to the results of the LR model curve-fitting, the estimated Archie’s parameter shows inversely proportional relationship with clay volumes. The estimated Archie’s parameter from the SMD model is sensitive to the lower frequency channels of the multifrequency dielectric logging tool. Nevertheless, utilizing the response of the dielectric logging tool in the frequency range, where interfacial polarization effect does not exist, can provide an alternative to estimate water saturation in shale formations with relatively less conductive waters.